Terminal Facilities Development Strategy Syukuran Aminuddin Amir Luwuk Airport - Suriyati Fatahuddin; Luthfi Samaduri; Siti Fauziah (Potensi: Jurnal Sipil Politeknik, 2024)
Banggai Regency is one of the mining areas in eastern Indonesia. Apart from that, there are also several natural tourist attractions spread across several areas in Banggai Regency, so that the flow of passengers and goods has increased from year to year. The availability of passenger facilities and airport activity services is a critical issue to pay attention to, without adequate facilities, airport service activities will be faced with a risk of meeting user needs. This research aims to determine the strategy for developing terminal facilities at Syukuran Aminuddin Amir Airport based on a combination of internal and external airport factors. The research method uses SWOT analysis with primary data sources in the form of distributing questionnaires and interviews with 100 respondents, as well as secondary data in the form of documents related to terminal facilities from the Airport UPT. The results of the analysis on the SWOT diagram show that the position of the airport is in diagram II, which means that even though it faces several threats, the company still has internal strength. The strategy that must be applied is a diversification strategy in which strength is used to overcome threats